Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
\(P=\left(x-y\right)^2+\left(x+y\right)^2-2\left(x+y\right)\left(x-y\right)-4x^2=\left(x-y-x-y\right)^2-\left(2x\right)^2=\left(-2y\right)^2-\left(2x\right)^2\)
\(=\left(2y-2x\right)\left(2y+2x\right)=2\left(y-x\right)2\left(y+x\right)=4\left(x+y\right)\left(y-x\right)\)
\(x^3-x^2y+3x-3y=x^2\left(x-y\right)+3\left(x-y\right)=\left(x-y\right)\left(x^2+3\right)\)
\(x^3-2x^2-4xy^2+x=x\left(x^2-2x+1-4y^2\right)=x\left[\left(x-1\right)^2-\left(2y\right)^2\right]=x\left(x+2y-1\right)\left(x-2y-1\right)\)
\(\left(x+2\right)\left(x+3\right)\left(x+4\right)\left(x+5\right)-8=\left(x^2+7x+10\right)\left(x^2+7x+12\right)-8\)
Đặt \(x^2+7x+10=t\), ta có:
\(t\left(t+2\right)-8=t^2+2t-8=t^2-2t+4t-8=t\left(t-2\right)+4\left(t-2\right)=\left(t-2\right)\left(t+4\right)\)
\(=\left(x^2+7x+10+4\right)\left(x^2+7x+10-2\right)=\left(x^2+7x+14\right)\left(x^2+7x-8\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1,Thực hiện phép tính :
a, (x + 2)9 : (x + 2)6
=(x+2)9-6
=(x+2)3
b, (x - y) 4 : (x - 2)3
=(x-y)4-3
=x-y
c, ( x2+ 2x + 4)5 : (x2 + 2x + 4)
=(x2+2x+4)5-1
=(x2+2x+4)4
d, 2(x2 + 1)3 : 1/3(x2 + 1)
=(2÷1/3).[(x2+1)3÷(x2+1)]
=6(x2+1)2
e, 5 (x - y)5 : 5/6 (x - y)2
=(5÷5/6).[(x-y)5÷(x-y)2]
=6(x-y))3
![](https://rs.olm.vn/images/avt/0.png?1311)
a ) \(\dfrac{x-y}{x^3+y^3}.Q=\dfrac{x^2-2xy+y^2}{x^2-xy+y^2}\)
\(\Leftrightarrow Q=\dfrac{x^2-2xy+y^2}{x^2-xy+y^2}:\dfrac{x-y}{x^3+y^3}\)
\(\Leftrightarrow Q=\dfrac{\left(x-y\right)^2}{x^2-xy+y^2}\cdot\dfrac{\left(x+y\right)\left(x^2-xy+y^2\right)}{x-y}\)
\(\Rightarrow Q=\left(x-y\right)\left(x+y\right)=x^2-y^2\)
Vậy \(Q=x^2-y^2\)
b ) \(\dfrac{x+y}{x^3-y^3}.Q=\dfrac{3x^2+3xy}{x^2+xy+y^2}\)
\(\Leftrightarrow Q=\dfrac{3x^2+3xy}{x^2+xy+y^2}:\dfrac{x+y}{x^3-y^3}\)
\(\Leftrightarrow Q=\dfrac{3x\left(x+y\right)}{x^2+xy+y^2}\cdot\dfrac{\left(x-y\right)\left(x^2+xy+y^2\right)}{x+y}\)
\(\Leftrightarrow Q=3x\left(x-y\right)=3x^2-3xy\)
Vậy \(Q=3x^2-3xy\)
Chọn đáp án D